Modelamiento de los estratos de consumo de energía eléctrica a través de análisis clúster en el barrio ciudad alegría de la ciudad de Loja - Briceño Preciado, Leonardo Yasmany (2022)
This research presents a classification by strata of energy consumption of the users of the “Ciudad Alegría” neighborhood in Loja, using grouping techniques. The methodology used allows the development of an exploratory data analysis to build groupings, converting a set of observations of variables in a specific grouping. Groupings that represent consumption patterns were obtained through the determination of demand variables like maximum demand, analysis of energy consumption and type of user. Furthermore, data mining and Matlab software, particularly the grouping techniques of the Dendrogram and K-means, were applied to identify the groupings that represent strata of energy consumption. Keywords: Energy consumption strata, Dendrogram, K-means.